2012
DOI: 10.3852/12-056
|View full text |Cite
|
Sign up to set email alerts
|

How well do ITS rDNA sequences differentiate species of true morels (Morchella)?

Abstract: Arguably more mycophiles hunt true morels (Morchella) during their brief fruiting season each spring in the northern hemisphere than any other wild edible fungus. Concerns about overharvesting by individual collectors and commercial enterprises make it essential that science-based management practices and conservation policies are developed to ensure the sustainability of commercial harvests and to protect and preserve morel species diversity. Therefore, the primary objectives of the present study were to: (i)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
52
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(56 citation statements)
references
References 63 publications
3
52
0
1
Order By: Relevance
“…Sequences generated in recent studies (Taşkın et al 2010, 2012; O’Donnell et al 2011; Du et al 2012a, 2012b) have been recorded in this site. The scientific community not only can freely download these sequences and access information for voucher specimens and/or cultures from this website, but also can contribute their validated sequences and information to the site.…”
Section: Species Diversity In Morchellamentioning
confidence: 84%
See 3 more Smart Citations
“…Sequences generated in recent studies (Taşkın et al 2010, 2012; O’Donnell et al 2011; Du et al 2012a, 2012b) have been recorded in this site. The scientific community not only can freely download these sequences and access information for voucher specimens and/or cultures from this website, but also can contribute their validated sequences and information to the site.…”
Section: Species Diversity In Morchellamentioning
confidence: 84%
“…Du et al (2012b) observed that the ITS- ef1-a-rpb1-rpb2 combined-gene data could successfully identify all the phylospecies in Morchella , with the ITS gene alone identifying 77.4% of them. Unfortunately, at least two-thirds of ITS sequences of Morchella in GenBank were found to be misidentified, a problem noted for other groups of fungi (Vilgalys 2003; Ryberg et al 2008).…”
Section: Species Diversity In Morchellamentioning
confidence: 99%
See 2 more Smart Citations
“…The uncertainty described above is an example of problems arising from attempts to accommodate morphologically defined species names to molecularly defined monophyletic groups. The inaccuracy in using of morphologically defined binomial species names to describe genetic diversity detected with molecular methods resulted in adoption of provisional system of species designations (see [7,24,[33][34][35][36]), where M. deliciosa is referred to as Mel-26 and M. esculenta as Mes-8. According to the newest data provided by Richard et al [12], the name Morchella conica is illegitimate at the species rank, while the Morchella elata status needs further study to be definitively resolved.…”
Section: Discussionmentioning
confidence: 99%